Association between HLA-B alleles and nevirapine-induced allergies among Indonesian HIV patients - Angela Satiti Retno Pudjiati; Dyah Ayu Mira Oktarina; Hardyanto Soebono; Saihas Sauda; Dewi Kartikawati Paramita; Iwan Dwiprahasto; Zubairi Djoerban (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
This study aimed to investigate the association between human leukocyte antigen-B(HLA-B) alleles and nevirapine allergy in HIV patients in Indonesia. A case control studywas conducted involving 147 HIV patients comprising of 50 patients with and 97patients without nevirapine allergy as control. The HLA-B allele typing was conducted byusing polymerase chain reaction-sequence specific oligonucleotide probes (PCR-SSOP),followed by sequencing. Bivariate analysis using Chi-square (X2) test and multivariatelogistic regression with significance level at p<0.05 were applied to analysis the data.Among 147 subjects, 34 with HLA-B alleles were identified. Bivariable analysis showedthat HLA-B*58 allele was the most significant risk factor for the nevirapine allergy (OR= 3.67; 95% CI: 1.79 to 7.54), while HLA-B*35 allele was a protective factor (OR =0.18; 95% CI: 0.08 to 0.42). Multivariate logistic regression analysis showed that youngmen and HLA-B*58 allele were the significant risk factors of nevirapine allergy (OR: 4.63;95% CI: 2.02 to 10.61), while older women with the HLA-B*35 was able to reducethe risk of nevirapine allergy approximately 81% (OR: 0.19; 95% CI: 0.08 to 0.49). Inconclusion, young male with the HLA-B*58 allele are the high risk factor for nevirapineallergy in Indonesian HIV patients.